Use of a negative pressure wound therapy system over closed incisions option in preventing post‐sternotomy wound complications. Issue 5 (29th March 2021) - Brega, Carlotta; Calvi, Simone; Albertini, Alberto
Abstract: Post‐sternotomy surgical site infections may be serious complications responsible for increased morbidity, mortality and length of hospital stay. A variety of wound‐healing strategies can be used over closed surgical incisions, including negative pressure wound therapy (NPWT). The aim of the study is to assess sternal wound complications after heart surgery using NPWT in patients at risk for surgical site complication. Considered risk factors affecting wound healing were type 2 diabetes, Body Mass Index (BMI) >30, chronic obstructive pulmonary disease (COPD), chronic renal failure (CRF) and myocardial revascularization by double mammary artery harvesting. With these premises, 90 patients were selected: 30 patients received traditional gauze dressings, 30 advanced dressings (hydrocolloid and carboxymethyl cellulose) and 30 patients NPWT. Thirty‐four patients (37.7%) had two risk factors, 41 patients (45.5%) were affected by three risk factors and 15 patients (16.6%) by four risk factors. The NPWT group had lower rates of diabetes and CRF and only one patient presented four risk factors. With regard to surgical times and types of surgical procedure, no significant differences were observed within the three groups. The patients who received NPWT over closed incision experimented a significantly lower rate of deep sternal complication over traditional gauze and hydrocolloid and carboxymethyl cellulose dressings.